2x ^ 3 - 7x ^ 2 = 0


x ^ 3 + x ^ 2 - 2x = 0


x ^ 4 - 16 = 0



(x ^ 4 - 1)(2x - 1) = 0​


Odpowiedź :

Odpowiedź:

odpowiedzi w załącznikach są dodatkowo podkreślone

Zobacz obrazek Xxxccc123

Odpowiedź:

[tex]2x^3-7x^2=0\\\\x^2(2x-7)=0\\\\x^2=0\ \ \ \ \vee\ \ \ \ 2x-7=0\\\\x=0\ \ \ \ \vee\ \ \ \ 2x=7\ \ /:2\\\\x=0\ \ \ \ \vee\ \ \ \ x=\frac{7}{2}\\\\\\x^3+x^2-2x=0\\\\x(x^2+x-2)=0\\\\x(x^2+2x-x-2)=0\\\\x(x(x+2)-(x+2))=0\\\\x(x+2)(x-1)=0\\\\x=0\ \ \ \ \vee\ \ \ \ x+2=0\ \ \ \ \vee\ \ \ \ x-1=0\\\\x=0\ \ \ \ \vee\ \ \ \ x=-2\ \ \ \ \ \ \vee\ \ \ \ x=1[/tex]

[tex]x^4-16=0\\\\x^4=16\\\\x=\sqrt[4]{16}\ \ \ \ \vee\ \ \ \ x=-\sqrt[4]{16}\\\\x=2\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-2\\\\\\(x^4-1)(2x-1)=0\\\\x^4-1=0\ \ \ \ \ \ \vee\ \ \ \ 2x-1=0\\\\x^4=1\ \ \ \ \ \ \ \ \ \ \ \ \vee\ \ \ \ 2x=1\ \ /:2\\\\x=\sqrt[4]{1}\ \ \ \ \ \ \vee\ \ \ \ x=-\sqrt[4]{1}\ \ \ \ \vee\ \ \ \ x=\frac{1}{2}\\\\x=1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-1\ \ \ \ \ \ \ \ \vee\ \ \ \ x=\frac{1}{2}[/tex]